Do anxiety levels and attitudes towards COVID-19 vaccines among healthcare workers change after COVID-19 vaccination? - Balaban, Hasan; Demirdağ Çevikkan, Meltem; Tanyeri Kayahan, Selin (The European Research Journal, 2023)
Objectives: The COVID-19 pandemic has significant effects on the mental health of societies and individuals worldwide while especially for healthcare workers these effects pose a higher risk due to occupational exposure. COVID-19 vaccines have been a turning point in the pandemic, however concepts as vaccine hesitancy and anti-vaccination have come into question again. This study aimed to comparatively evaluate the attitudes of healthcare professionals towards the COVID-19 vaccines, their pandemic-related anxiety and phobia levels before and after vaccination. Methods: In this cross-sectional study, the anxiety levels and attitudes towards COVID-19 vaccines of healthcare professionals working in a state hospital were evaluated by administrating Coronavirus Anxiety Scale (CAS), Coronavirus-19 Phobia Scale (CP19-S), and Attitudes Towards COVID-19 Vaccine Scale (ATV-COVID-19) to the participants both in the pre-vaccine (n = 154) and post-vaccine (n = 81) periods. All these scales were previously validates in Turkish population. 44.8% (n = 69) of pre-vaccine sample and 45.7% (n = 37) of post-vaccine sample were female and all participants were Turkish. Participants were questioned about COVID-19 symptoms during each application and kept in touch in terms of side effects. Results: One hundres fifty-four pre-vaccine and 81 post-vaccine health workers were included in the study. After the vaccination scores of CAS and CP19-S decreased significantly compared to the pre-vaccine period (p < 0.001 and p = 0.005, respectively); while ATV-COVID-19 scores significantly increased (p < 0.001). Participants did not report significant adverse events in the post-vaccine period. Conclusions: The results of the study in the form of a decrease in anxiety and fear levels and an increase in positive attitudes towards the vaccine after vaccination suggest that vaccination may have a positive effect on the mental health of healthcare workers.